Cancer mortality in a synthetic spinning plant in Besançon, France. Issue 9 (16th January 2007) - Hours, M; Févotte, J; Lafont, S; Bergeret, A
Abstract : Objectives: To assess the mortality of a cohort of workers in a synthetic textile spinning plant and to evaluate the relationship between mortality from lung, liver and bladder cancer and the processes or the products used. Methods: The study population consisted of male workers present for at least 6 months in the plant from 1968 to 1984. The cohort was followed until 1999. Vital status and the causes of death were determined by consulting national registries. The population of the Franche-Comté region was used for comparison. In total, 17 groups of exposure were assessed by the industrial hygienist, based on the consensus of an expert group that determined the exposure levels of each job to selected occupational hazards. Each worker was assigned to one or several groups, according to his occupational history. Confounding factors could not be assessed. Standardised mortality ratios (SMR) and 95% bilateral confidence intervals were calculated based on an assumed Poisson distribution of the number of cases to compare the plant mortality and the population mortality. Internal analyses were performed with Cox models in order to assess the risks of death related to the various exposures. Results: In the whole cohort, mortality from all malignant neoplasms was lower than expected, but this was not significant. All the estimated SMRs were lower than or close to 1. The "hot -line fitters" (RR = 2.13; n = 9; 1.06 to 4.29) and the "fibre-drawing workers" (RR = 1.83; n = 20;1.09 to 3.07) experienced a statistically significant excess in mortality from lung cancer. A slightly elevated but not significant risk of death related to lung cancer (RR = 1.5; n = 41; 0.8 to 2.7) was observed in the groups with the highest exposure to mineral fibres. A statistically significant increase in cancer deaths was observed for workers with high exposure to dust (higher intensity: RR = 1.42; n = 79; 1.06 to 1.89). Conclusion: Some findings, mainly of lung cancer, justify further exploration in other plants in this industry,